Glutathione S-transferase (GSTT1 and GSTP1) Polymorphisms Improves the Short- and Long-Term Efficacy of Concurrent Chemoradiotherapy in Advanced Ovarian Cancer - Xiao Xu; Zhuo Zhong; Dong-Mei Dou; Fenfen Li (Molecular Biology & Nanomedicine, 2020)
Over the past four decades, patients with advanced ovarian cancer (OC) has enjoyed greatly improved survival rate considering advances in combined chemotherapy with platinum and paclitaxel. We investigated the association between polymorphisms within glutathione S-transferase genes (GSTM1, GSTT1 and GSTP1) and short- and long-term efficacy of concurrent chemoradiotherapy (CCRT) in advanced OC. Patients with advanced OC and healthy females were selected in our study. Multiplex polymerase chain reaction (PCR) and PCR-restriction fragment length polymorphism (PCR-RFLP) were applied to detect homozygous deletions in GSTM1 and GSTT1, as well as codon 105 genetic polymorphisms in GSTP1 exon 5. All the patients with advanced OC were treated with CCRT. Toxicity of chemotherapy, short-term efficacy, recurrence and metastasis, respectively. Long-term survival outcomes were checked with a further examination and all patients were followed up for three years after CCRT.Compared with healthy females, patients with advanced OC showed higher frequencies of GSTT1 non-null genotype and homozygous mutation type GG of GSTP. GSTP1genetic polymorphisms were relevant to neutropenia resulted from CCRT in patients with advanced OC. Compared with patients with GSTT1non-null genotype, those with GSTT1 null genotype appeared to enjoy a better short-term efficacy, lower recurrence and metastasis rate, higher survival rate and longer mean survival time. Compared with patients with GG genotype, those with GSTP1 AA + AG genotype also enjoyed more positive results. Our results reveal that GSTT1 null genotype and GSTP1AA + AG genotype are associated with short- and long-term efficacy of CCRT in advanced OC.